(untitled) (International Journal of Engineering and Computer Science, 2020)
Today very important issue is to hide our sensitive data which comes under data hiding which means hiding our sensitive data as well as information from out side world. Image will become an important and sensitive information when it contain any sensitive information in it for many reasons like communication owner identification etc. Many techniques have been introduces one of which is image morphing which means changes its form from one to another without changing its other parameter to make it more secure . For morphs between faces, the metamorphosis does not look good if the two faces do not have the same shape approximately. In this project, we implemented a morphing scheme which would combine cross-dissolve with warping methods to give good morphs. This is based on "Feature-Based Image Metamorphosis. The morph process consists of a warping stage before cross-dissolving so that the two images have the same shape. The warp is specified, in this case, by a mapping between lines in the first and second images. In the following discussion, the first image will be called the source image and the last image will be called the destination image. In this survey paper we will show you different types of morphing algorithms, procedures and techniques.